O uso do tempo livre e sua relação com a qualidade de vida no envelhecimento - Peralta, Adriana (2020)
A change in the demographic and epidemiological profile has been occurring in Brazil and the growing number of elderly people in society demonstrate the need of studies in gerontology field over the relationship between quality of life and the use of free time by the elderly. Some elderly seeks to adapt their time in search of new perspectives of life and, above all, try to adapt to the new world that is presented nowadays. In this new and historic moment, the elderlies, who are willing to readjust themselves to obtain quality of life, are our great challenge. Research on the use of free time with the elderly become relevant, since it can demonstrate lifestyle, perceived performance of daily activities and how these activities relates with quality of life. Therefore, the main objective of this study is to evaluate the use of free time by the elderly and its relationship with quality of life. As for the specific objectives, we seek in this population: to identify the socioeconomic profile; identify which activities they perform in their free time; evaluate quality of life; and relate the quality of life with the use of free time. This is a cross-sectional analytical study with a quantitative approach. The research was conducted at the Serviço Social do Comércio do Rio Grande do Sul (SESC/RS), in the Maturity Active Program, which promotes social groups of elderly in the city of Porto Alegre, Rio Grande do Sul. It was a convenience sample and the variables were analyzed using descriptive statistics. This study was approved by the institution involved (SESC / RS), Scientific Committee of the Institute of Geriatrics and Gerontology of the Pontifical Catholic University of Rio Grande do Sul (IGG/PUCRS), Research Ethics Committee of PUCRS and has the Covenant Additive Term Agreement accepted by the representative of the School of Medicine. The data were collected through the WHOQOL-OLD questionnaire, socio-demographic and economic questionnaire, and the instrument “Communication, technology and aging”, referring to the use of free time, which contain the information used in this study. The questionnaires and instrument were answered by selected elderly through the invitation of the group coordinator of the institution in which the study was developed. After agreeing to participate in the research, the elderly signed the Informed Consent Form (ICF). This study has reached as conclusion the use of free time is associated with of quality of life.